Combined role of lymph node ratio and serum thyroglobulin levels in predicting prognosis of papillary thyroid carcinoma. Issue 8 (August 2020) - Jeon, Subin; Kwon, Seong Young; Ryu, Young Jae; Kang, Sae-Ryung; Yoo, Su Woong; Cho, Sang-Geon; Kim, Jahae; Song, Ho-Chun; Sohn, Seok-Joon; Bom, Hee-Seung; Min, Jung-Joon
Abstract : Objectives: The aim of this study was to evaluate a prognostic value of the extent of metastatic lymph node combined with TSH-stimulated serum thyroglobulin (sTg) measured just before radioactive iodine (RAI) therapy in patients with papillary thyroid cancer (PTC). Methods: The retrospective study included 468 patients with PTC who underwent total thyroidectomy with neck dissection and postoperative RAI therapy. The extent of metastatic lymph node was evaluated with the lymph node ratio (LNR) which was defined as the number of metastatic lymph nodes out of the number of total removed lymph nodes. We investigated which factors could significantly predict persistent or recurrent disease (PRD). Results: LNR ≥0.4 ( P  = 0.002) and sTg ≥6.0 ng/mL ( P  < 0.001) were associated with PRD in univariate analysis. In multivariate analysis, only male [hazard ratio: 2.35, 95% confidence interval (CI): 1.18–4.66, P  = 0.014] and sTg (hazard ratio: 9.35, 95% CI: 4.44–19.67, P  < 0.001) were associated with PRD prediction. When we divided patients into two groups (patients with sTg level < 6.0 ng/mL and those with sTg level ≥ 6.0 ng/mL), LNR (≥0.4) was a significant predictor of PRD in patients with sTg <6.0 ng/mL (hazard ratio: 4.38, 95% CI: 1.22–15.72, P =  0.024). Conclusions: LNR ≥0.4 was a significant predictor of PRD when the sTg level was <6.0 ng/mL. LNR should be used in combination with a relatively low level of serum sTg to predict the prognosis of patients with PTC.